Evaluation of Anti-Inflammatory and Analgesic Activities of Ethanolic Stem Extract of Abutilon crispum: An In Vitro Study (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Inflammation and pain are interrelated physiological responses that contribute to the pathogenesis of various acute and chronic diseases. This study evaluates the anti-inflammatory and analgesic potential of the ethanolic stem extract of Abutilon crispum (EEAC), a plant traditionally recognized for its medicinal properties, though its stem remains largely unexplored scientifically. The cytotoxicity profile of EEAC was assessed using the MTT assay on LPS-stimulated macrophages. EEAC exhibited high cell viability (>82%) even at the highest tested concentration (100 µg/mL), indicating strong cytocompatibility and suggesting mitochondrial protection. Anti-inflammatory activity was evaluated by quantifying nitric oxide (NO) levels using the Griess method. LPS-induced NO production (20.19 ± 0.22 µM/mL) was significantly reduced following EEAC treatment (17.45 ± 0.19 µM/mL), implying suppression of inducible nitric oxide synthase (iNOS) and potential modulation of the NF-κB signaling pathway. Furthermore, EEAC demonstrated notable analgesic activity by inhibiting prostaglandin E₂ (PGE₂) production. PGE₂ levels in LPS-induced cells (2206.2 ± 19.45 pg/mL) were reduced to 1101.4 ± 13.49 pg/mL upon EEAC treatment, suggesting inhibition of cyclooxygenase-2 (COX-2) activity. Although less potent than indomethacin (189.4 ± 3.39 pg/mL), EEAC exhibited a moderate yet promising analgesic effect. Overall, the extract’s bioactivity appears to involve antioxidant defense mechanisms, suppression of key inflammatory mediators (NO and PGE₂), and cellular protection. These findings support the potential of EEAC as a natural therapeutic agent with dual anti-inflammatory and analgesic properties, warranting further investigation for plant-based interventions in inflammatory disorders.